Soybean seed quality in different production environments - Zambiazzi, Everton Vinicius (2017)
The research was performed with aiming to increase knowledge in production and technology area of soybean seeds. The goal was to evaluate the yield of different soybean cultivars, the quality of freshly harvested and stored seeds produced in different soybean cultivars and crop environments in Minas Gerais state, as well as the stability of soybean cultivars. Seeds were produced in three locations in Minas Gerais state (Lavras, Inconfidentes and Patos de Minas) in 2013/14 and 2014/15 seasons, evaluating 17 soybean cultivars. In addition, after harvest yield and seeds quality were evaluated in two periods (freshly harvested and eight months after storage), quantifying water content, germination in substrate paper and sand, seedling emergence, speed emergency index, mechanical damage by sodium hypochlorite, electrical conductivity, speed aging, vigor and viability of seeds by tetrazolium test and seeds sanity. Experimental precision was performed by accuracy selective estimates (rgg') and coefficient of variation (CV). Seeds produced in Lavras environment were the most productive and with higher quality in the two evaluation periods. Higher yields and higher quality for seeds were observed in 2013/14 seasons. TMG 1179 RR, CD 2737 RR and CD 237 RR cultivars were more stable associating high yield and quality, independent of production environment variations and season for recently harvested and stored seeds. It was also the goal to estimate parameters related to soybean seeds yield and quality in genotypes grown in different environments in Minas Gerais state as well as to evaluate interaction effect of genotype x environment (GxE) for soybean seeds yield and quality. Seeds were produced in three locations in Minas Gerais state (Lavras, Inconfidentes and Patos de Minas) in 2013/14 and 2014/15 seasons, evaluating 17 soybean genotypes. Seed yield and quality were evaluated for germination in substrates paper and sand, seedling emergence, speed emergency index, mechanical damage by sodium hypochlorite, electrical conductivity, speed aging, vigor and viability of seeds by tetrazolium test. Quadratic component genotypic, GXE variance component, genotype determination coefficient, genetic variation coefficient and environmental variation coefficient were estimated using Genes software. Percentage analysis of genotypes contribution, environments and genotype x environment interaction were conducted by sites combination two by two and three sites combination, using software R. Considering genotypes selection of broad adaptation, TMG 1179 RR, CD 2737 RR and CD 237 RR associated better yield performance at high physical and physiological potential effect of seed. Environmental effect was more expressive for most of the characters related to soybean seed quality. Genotypes x environment interaction effects were expressive though genotypes did not present coincidental behavior in different environments. GxE interaction presence suggests soybean genotype selection for yield and seed quality was conducted in different locations and season suggested by GxE interaction presence aiming to mitigate characters effect expression though, these characters expression for the most part was due to environmental effects.